Multimodal word-search trajectories in L2 interaction: The use of gesture and how it changes over time - Skogmyr Marian, Klara; Pekarek Doehler, Simona (My University, 2022)
This paper investigates the temporal dynamics of bodily and vocal conduct in the course of L2 word searches. Based on a longitudinal dataset of L2 French conversations, we first identify a recurrent multimodal search-trajectory involving specific simultaneous and successive assemblies of hand movements/holds with gaze, and (para)verbal displays of ongoing search. We interpret these Gestalt-like trajectories as part of methodic practices through which speakers both account for breaks in progressivity and display their search as “solitary”, preempting recipient’s entry into the turn-in-progress. We then put our findings into a longitudinal perspective, showing how features of these assemblies change over time in the developmental trajectories of L2 speakers.
Keywords: Word searches; gestures; social interaction; L2 French; development